EFFECTIVENESS OF VARIOUS CROP REGULATION TREATMENTS IN GUAVA (PSIDIUM GUAJAVA) CV. ALLAHABAD SAFEDA - SHARMA, ARTI; V. K. , WALI; SHARMA, BINDIYA (The Bioscan, 2016)
Crop regulation treatments viz. Leaf pair pruning (retaining one, two and three leafs), GA3 sprays (100,150 and 200ppm) at flower bud differentiation stage and NAA (600 ppm) at flowering (control) were used to regulate rainy season crop in guava cv. Allahabad Safeda. One leaf pair pruning resulted into maximum yield reduction in rainy season with subsequent maximum yield (73.05, 72.04 and 76.40 kg during 2010, 2011 and 2012, respectively) and fruit weight (221.70, 205.39 and 226.12 during 2010, 2011 and 2012, respectively) in winter season. Plants with one leaf pruning produced better quality fruits in both the seasons and recorded maximum TSS (12.00,11.80 and 12.40oB during rainy season and 13.73, 12.80 and 13.40 oB during winter season of 2010, 2011 and 2012, respectively and Ascorbic acid ( 210.30, 201.65 and 205.66mg/100g during rainy season and 259.66, 199.67 and 240.45 mg/100g during winter season of 2010, 2011 and 2012, respectively) and minimum acidity (0.52,0.51 and 0.49 % during rainy season and 0.48, 0.47 and 0.45 during winter season of 2010, 2011 and 2012, respectively). Overall profit was also highest in one leaf pair pruning by withholding rainy season crop. Thus it was concluded that rainy season crop of guava should be avoided by using one leaf pair pruning.